La diaspora des morisques d’Espagne, 1609‑1614 - Bernard Vincent (Diasporas: Circulations, Migrations, Histoire)
The expulsion of Moriscos from all of Spain, declared on 4th April 1609, created modern Europe’s greatest diaspora as it affected between 250 and 280 thousand people. Il was carried out in stages between 1609 and 1614. The Moriscos, descendants of Muslims who were converted by force a century earlier, settled in both Muslim and Christian countries in the Mediterranean, although mostly in the Maghreb, from Rabat-Salé to Tunis.